2017
DOI: 10.1038/s41598-017-01518-5
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the evolutionary mechanism of the chloroplast genome size by comparing whole-chloroplast genome sequences in seed plants

Abstract: The chloroplast genome originated from photosynthetic organisms and has retained the core genes that mainly encode components of photosynthesis. However, the causes of variations in chloroplast genome size in seed plants have only been thoroughly analyzed within small subsets of spermatophytes. In this study, we conducted the first comparative analysis on a large scale to examine the relationship between sequence characteristics and genome size in 272 seed plants based on cross-species and phylogenetic signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 95 publications
8
79
0
Order By: Relevance
“…Chloroplast genome content and structure are reviewed for example in [4,5]. Chloroplast genomes are widely used for evolutionary analyses [6,7], barcoding [8,9,10], and meta-barcoding [11,12]. Interesting aspects of chloroplast genomes are their small size (120 kbp to 160 kbp, [1]), caused through endosymbiotic gene transfer [13,14] and the low number of 100 to 120 genes that are still encoded on the chloroplast genome [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast genome content and structure are reviewed for example in [4,5]. Chloroplast genomes are widely used for evolutionary analyses [6,7], barcoding [8,9,10], and meta-barcoding [11,12]. Interesting aspects of chloroplast genomes are their small size (120 kbp to 160 kbp, [1]), caused through endosymbiotic gene transfer [13,14] and the low number of 100 to 120 genes that are still encoded on the chloroplast genome [4].…”
Section: Introductionmentioning
confidence: 99%
“…The prospective of chloroplast phylogenomics to resolve contentious phylogenetic relationships, at nearly all taxonomic levels, have been proven over the recent past, e.g., in providing strong support for the evolutionary clades of the basal Angiosperms [4,7], the earlydiverging eudicots [8,23], and the early-diverging monocots [6]. Furthermore, through comparative phylogenomics, the availability of complete chloroplast genome sequences have significantly contributed to our understanding of genome evolutionary patterns driven by events such as gene transfers, duplications, and rearrangements [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In terrestrial plants, the cpDNA varies between ≈120,000 and ≈160,000 bp (PALMER, 1995). For Gymnosperm, the size of cpDNA the chloroplast genome is significantly lower than for Angiosperm (XIAO-MING et al, 2017) and, for Eucalyptus spp. and another superior genus, cpDNAs with around 160,000 bp are commonly observed (EGUILUZ et al, 2017;LI et al, 2017;PAIVA et al, 2011;SAINA et al, 2018;STEANE et al, 2005 Regarding the cpSSR regions identified, the majority were classified as mononucleotides.…”
Section: Resultsmentioning
confidence: 94%
“…The size range observed in cpDNAs of closer species can be attributed to variations in intergenic regions length, that can be associated to species evolution process (XIAO-MING et al, 2017). In terrestrial plants, the cpDNA varies between ≈120,000 and ≈160,000 bp (PALMER, 1995).…”
Section: Resultsmentioning
confidence: 99%